STRENGTH DEVELOPMENT OF PLAIN CONCRETE SLABS BY THE SUSTAINABILITY POTENTIAL OF LEAD-LOADED RICE HUSK (LLRH) - Abbas, Firas Saeed; Abdulkareem, Wael Shahadha; Abbas, Mohammed Nsaif (Journal of Applied Engineering Science, 2022)
The production of environmentally friendly, sustainable plain concrete slabs is an essential requirement in this work. It is interesting to note that the ions of lead of wastewater loaded into rice husks can be used as an additive for plain concrete slabs to improve the flexural strength, as well as the workability of plain concrete slabs (or walls), which are produced by using Lead-loaded rice husk material as an additive substance in protective shields for the establishment of hospital radiology rooms. The results show that flexural strength for plain concrete slabs begins with a relative increase until it reaches breakdown. The results at age of 28 days also show that by increasing the proportion of Lead-loaded rice husk added to plain concrete slabs, the flexural strength gradually increases until it reaches one-third of the value of reference plain concrete slabs at a specific ratio, then decreases sharply until the slabs fail. These results provide a novel approach to managing toxic waste and propose an easy, simple, effective, economical, and environmentally friendly way to get rid of more than one type of waste and reach the concept of zero residue level.
Keywords: plain concrete slabs, flexural strength development, lead-loaded rice husk (LLRH), adsorbent waste additive, zero residue level, sustainability development